Association between perceived racial discrimination and hypertension: findings from the ELSA-Brasil study - Mendes, Patrícia Miranda (2018)
Fundação Oswaldo Cruz. Escola Nacional de Saúde Pública Sérgio Arouca. Rio de Janeiro, RJ. Brasil / Universidade Federal do Pará. Belém, PA, Brasil.